Characterisation of the immune response to calcium phosphate particulates; implications for osteoarthritis and bone tissue engineering - MAHON, OLWYN (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2020)
Early trauma, resulting in focal areas of cartilage damage with injury to the underlying subchondral bone (osteochondral damage) often progresses to arthritis. These so called osteochondral defects (OCDs) can arise from an acute traumatic injury to the knee or an underlying disorder of the bone. If left untreated, localised OCDs can become widespread and often progress to more severe damage, as is the case in Osteoarthritis (OA). It is now widely accepted that cartilage damage in OA is associated with inflammation and a number of ?damage? or ?danger? associated molecules have been identified that contribute to this phenotype. They include hyaluronic acid fragments, basic calcium phosphate (BCP) crystals and members of the S100 family of proteins. As joint damage progresses, total joint replacement (TJR) is required to relieve pain and restore joint function, however TJRs themselves are associated with long-term complications such as periprosthetic osteolysis (PO) which is driven by implant-derived wear debris particles that are generated over time causing inflammation and eventual implant failure. With this in mind, efforts are underway to (i) improve the biocompatibility and durability of orthopaedic implants and (ii) to develop tissue engineering strategies that can repair early osteochondral damage, before OA progresses. The most promising approach is to develop biomaterial scaffolds that promote self-repair and regeneration of damaged tissue. However, as with traditional implant materials, tissue engineered constructs can also impact host immune responses and it has become increasingly apparent that engineering a pro-regenerative immune response following scaffold implantation is integral to functional tissue regeneration. This study aimed to investigate the direct effects of endogenous and exogenous calcium phosphate particulates in human macrophages. These particulates include OA-associated BCP crystals and hydroxyapatite (HA), which is commonly used as a coating for orthopaedic implants and bone tissue engineering applications. The data presented here demonstrates that BCP crystals drive pro-inflammatory M1 macrophage polarization and metabolic reprogramming, causing cells to derive energy from glycolysis rather than oxidative phosphorylation, a phenomenon that is emerging as a key regulator of macrophage phenotype. This study therefore, not only provides further insight into how OA-associated DAMPs impact on immune cell function, but also highlights metabolic reprogramming as a potential therapeutic target for calcium crystal-related arthropathies. This study also examined the specific signalling pathways activated by wear particles in primary human macrophages. As was the case for BCP crystals, HA and PMMA (i.e. bone cement) particles were found to drive M1 macrophage polarization and this was shown to be dependent on activation of the membrane proximal kinase, Spleen Tyrosine Kinase (Syk), in addition to members of the mitogen-activated protein kinase (MAPK) family of signalling molecules. Pre-treatment of macrophages with Syk or MAPK inhibitors, not only prevented macrophage polarization, but also attenuated production of key pro-inflammatory mediators that have been specifically implicated in periprosthetic osteolysis and osteoclast differentiation. While further investigation is required, this study identifies these molecules as potential therapeutic targets to treat, or possibly prevent wear debris induced inflammation. Finally, an immune modulating scaffold for bone defect healing containing nanoHA particles was developed. In contrast to micron sized HA particles, the in-house generated nano particles were shown to preferentially polarize human macrophages towards an M2 phenotype. Furthermore, nano-particle-mediated IL-10 induction by macrophages resulted in enhanced mesenchymal stem cell (MSC) osteogenesis in vitro, demonstrating for the first time, a direct pro-osteogenic role for this cytokine. Implantation of particle-functionalised scaffolds into a rat femoral defect resulted in a more anti-inflammatory, pro-regenerative phenotype at the site of implantation, compared to the pro-inflammatory, fibrotic environment observed with micron-HA functionalised scaffolds. The anti-inflammatory response induced by nanoHA particles also correlated with enhanced tissue vascularisation and increased bone repair demonstrating that nano HA particles have inherent immune-modulatory properties. Overall, this study demonstrates that a greater understanding of the immune response to particulate matter generated from endogenous processes in the joint, or from biomaterial implants is required. This may allow for the identification of novel therapeutic targets for joint-associated inflammation or for the development of superior implant materials that can ultimately be used to improve the bone tissue repair and regeneration process in a disease that is becoming steadily more prevalent as the aging population increases.
APPROVED
Keywords: Tissue engineering; Osteoarthritis; Bone tissue